Mass Exchange of Water and Soil on the Soil Surface in the Rainfall Splash Erosion - Sanxiang, Sun; Yunxia, Zhang; Pengshui, Lei (Frontiers in Earth Science, 2021)
This research aims to unfold the mass exchange mechanism of water and soil on the soil surface in the rainfall splash erosion process. We regard the rainfall splash erosion process as a collision process between the raindrop and the soil particle on the soil interface. This recognition allows us to incorporate research approaches from the spring model, which has been developed for analyzing collision process between solid and solid objects, and between liquid and solid objects; from the spring vibrator model, which has been developed for explaining the process of the droplets impacting the super-hydrophobic surface; and the mass-spring model, which has been developed for simulating the impact of liquid drops on solid surface. We further argue that because a same set of factors determine the splash amount and infiltration amount and it is relatively simpler to observe the infiltration amount, an investigation into the relationship between the splash amount and infiltration amount would be able to provide a new channel for quantifying the splash erosion. This recognition leads us to examining the relationship between single raindrop, rainfall kinetic energy and splash erosion from both theoretical and empirical angles, with an emphasis on the relationship between the infiltration amount and the splash erosion. Such an investigation would add value to the collective effort to establish mass exchange law in water-soil interface during rainfall splash erosion.It is found that during the rainfall splash process, the splash erosion is proportional to the rainfall kinetic energy; and has a linear relation to the infiltration amount, with the rainfall intensity as one of important parameters and the slope depending on the unit conversation of the infiltration amount and the splash erosion. If the units of two items are same, the slope is the ratio of the soil and water density, and the splash erosion velocity of the rainfall is half of the rainfall terminal velocity. The single raindrop kinetic energy and the splash erosion have a quadratic parabola relation, and the splash velocity is about 1/3 of single raindrop terminal velocity.